Optimalization Strategy of Instagram Content to Increase Engagement in Building Brand Awareness at PT Citi Asia Internasional - Ranjika Daud Hanapi; Erlita Ridanasti (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the content strategy implemented by PT Citi Asia Internasional on Instagram to increase audience engagement as an effort to build brand awareness. In the digital era, social media has become a crucial tool for companies to reach consumers or partners directly, especially through Instagram, which is characterized by its visual and interactive nature. This research employs a qualitative narrative approach with data collection techniques including observation, interviews, and documentation of PT Citi Asia Internasional’s official Instagram account. The results of the study show that the use of consistent, interactive, and audience-relevant content strategies positively contributes to increased engagement, which indirectly strengthens brand awareness. Optimization through visual elements, compelling captions, and the use of Instagram features such as stories, reels, and carousels has also proven effective in building closer communication with followers. Thus, a well-planned and trend-adaptive content strategy becomes the key to creating a strong relationship between the brand and its audience on social media.